From digitized whole‐slide histology images to biomarker discovery: A protocol for handcrafted feature analysis in brain cancer pathology - Xuanjun Lu; Yawen Ying; Jing Chen; Zhiyang Chen; Yuxin Wu; Prateek Prasanna; Xin Chen; Mingli Jing; Zaiyi Liu; Cheng Lu (Brain-X, 2025)
Abstract Hematoxylin and eosin (H&E)‐stained histopathological slides contain abundant information about cellular and tissue morphology and have been the cornerstone of tumor diagnosis for decades. In recent years, advancements in digital pathology have made whole‐slide images (WSIs) widely applicable for diagnosis, prognosis, and prediction in brain cancer. However, there remains a lack of systematic tools and standardized protocols for using handcrafted features in brain cancer histological analysis. In this study, we present a protocol for handcrafted feature analysis in brain cancer pathology (PHBCP) to systematically extract, analyze, model, and visualize handcrafted features from WSIs. The protocol enabled the discovery of biomarkers from WSIs through a series of well‐defined steps. The PHBCP comprises seven main steps: (1) problem definition, (2) data quality control, (3) image preprocessing, (4) feature extraction, (5) feature filtering, (6) modeling, and (7) performance analysis. As an exemplary application, we collected pathological data of 589 patients from two cohorts and applied the PHBCP to predict the 2‐year survival of glioblastoma multiforme (GBM) patients. Among the 72 models combining nine feature selection methods and eight machine learning classifiers, the optimal model combination achieved discriminative performance with an average area under the curve (AUC) of 0.615 over 100 iterations under five‐fold cross‐validation. In the external validation cohort, the optimal model combination achieved a generalization performance with an AUC of 0.594. We provide an open‐source code repository (GitHub website: https://github.com/XuanjunLu/PHBCP) to facilitate effective collaboration between medical and technical experts, thereby advancing the field of computational pathology in brain cancer.